Intratubular, Intracellular, and Mitochondrial Angiotensin II/AT1 (AT1a) Receptor/NHE3 Signaling Plays a Critical Role in Angiotensin II-Induced Hypertension and Kidney Injury - Li, Xiao Chun; Wang, Chih-Hong; Leite, Ana Paula Oliveira; Zhuo, Jia Long (Frontiers in Physiology, 2021)
Hypertension is well recognized to be the most important risk factor for cardiovascular diseases, stroke, and end-stage kidney failure. A quarter of the world’s adult populations and 46% of the US adults develop hypertension and currently require antihypertensive treatments. Only 50% of hypertensive patients are responsive to current antihypertensive drugs, whereas remaining patients may continue to develop cardiovascular, stroke and renal diseases. The mechanisms underlying the poorly controlled hypertension remain incompletely understood. Recently, we have focused our efforts to uncover additional renal mechanisms, pathways, and therapeutic targets of poorly controlled hypertension and target organ injury using novel animal models or innovative experimental approaches. Specifically, we studied and elucidated the important roles of intratubular, intracellular and mitochondrial angiotensin II (Ang II) system in the development of Ang II-dependent hypertension. The objectives of this article are to review and discuss our recent findings that: a) circulating and intratubular angiotensin II (Ang II) is taken up by the proximal tubules via the (AT1) AT1a receptor-dependent mechanism; b) intracellular administration of Ang II in proximal tubule cells, or adenovirus-mediated overexpression of an intracellular Ang II fusion protein selectively in the mitochondria of the proximal tubules induces blood pressure responses; and c) genetic deletion of AT1 (AT1a) receptors or the Na+/H+ exchanger 3 (NHE3) selectively in the proximal tubules decreases basal blood pressure and attenuates Ang II-induced hypertension. These studies provide a new perspective into the important roles of the intratubular, intracellular, and mitochondrial angiotensin II/AT1 (AT1a) receptor signaling in Ang II-dependent hypertensive diseases.